The lipopolysaccharide from Escherichia coli O127:B8 induces inflammation and motility disturbances in rabbit ileum - Laura Grasa; Sergio Gonzalo; Alba de Martino; María Divina Murillo (World Rabbit Science, 2017)
The aim of this work was to evaluate the effects of lipopolysaccharide (LPS) from Escherichia coli O127:B8 on the expression of toll-like receptor 4 (TLR4), the histology, and motor function in rabbit ileum. Rabbits were injected intravenously with saline or LPS (100 μg/kg, 2 h). The mRNA expression and localization of TLR4 were determined by reverse transcriptase-PCR and immunofluorescence, respectively. Histological damage induced by LPS was evaluated in sections of ileum stained with haematoxylin and eosin. Contractility studies of ileum were performed in an organ bath. The mRNA expression of TLR4 decreased in the muscular but not in the mucosal layer of rabbits treated with LPS. TLR4 was localised in both the mucosal and muscular layers of rabbit ileum. LPS induced intestinal inflammation and altered the spontaneous contractions and the serotonin-, acetylcholine- and KCl-induced contractions. In conclusion, LPS from E. coli O127:B8 induced a decrease in the mRNA expression of TLR4, an inflammatory response, and changes in the contractility of rabbit ileum.